Efficacy of Hyperthermic Intraperitoneal Chemotherapy and Cytoreductive Surgery in the Treatment of Recurrent Uterine Sarcoma. Issue 6 (1st June 2018) - Díaz-Montes, Teresa P.; El-Sharkawy, Farah; Lynam, Sarah; Harper, Amy; Sittig, Michelle; MacDonald, Ryan; Gushchin, Vadim; Sardi, Armando
Abstract : Objective: Uterine sarcomas (USs) are characterized by poor response to systemic chemotherapy and high recurrence rates. This study evaluates whether the use of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) confers survival benefit in comparison with conventional treatment modalities in patients with recurrent US. Methods/Materials: A retrospective analysis of patients with recurrent US at a single institution for an 11-year study period was performed. All women with a pathologic diagnosis of leiomyosarcoma, adenosarcoma, endometrial stromal sarcoma, or undifferentiated US were identified. Overall and disease-free survival was estimated using Kaplan-Meier method. Comparisons between the study groups were performed with the log-rank test and Cox regression. Results: A total of 26 patients were identified. Five patients received chemotherapy and/or radiotherapy without surgical intervention, 14 patients underwent surgery alone or a combination of surgery and adjuvant systemic chemotherapy, and 7 patients received cytoreductive surgery with HIPEC. There was no treatment-related mortality in any group, and only 1 patient had grade III–IV surgical complications. Median disease-free survival was 2.4 months for patients with nonsurgical treatments, 5.3 months for patients treated with conventional surgery, and 11.3 months for patients treated with HIPEC. Median overall survival was 35.9 months for patients treated with conventional surgery and 43.8 months for patients treated with HIPEC. Conclusions: Our study is the first to compare survival outcomes of HIPEC versus conventional therapies for recurrent US and is suggestive of treatment benefit. Further studies with more patients and longer follow-up to evaluate the role of HIPEC in management of this disease are warranted.